Level of psychological security among a sample of university students of Tishreen during the Syrian cries "A field study in Latakia city" - Chrebah, Bouchra (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The current research aimed to recognize the level of psychological security among a sample of Tishreen university students. In order to achieve the objective of this research, Shkeer’s psychological security scale was applied, which its factor structure was investigate by the researcher in a previous study. The scale was used for data collection, and in year 2017-2018, a sample of (233) students participated in the research. The results showed that the level of students’ psychological security is medium, and there is no difference between males and females, but there are differences according to the specialty, especially in “practice life”, where that the students of practice specialty showed higher feeling of psychological security than the students of theoretic specialty.